Stable isotopes of carbon (δ13C) and oxygen (δ18O) from vaquita (Phocoena sinus) bones as indicators of habitat use in the Upper Gulf of California - Rodríguez-Pérez, Mónica-Yanira; Sánchez-Velasco, Laura; Rosas-Hernández, Martha-Patricia; Hernández-Camacho, Claudia J.; Cervantes, Fernando A.; Gallo-Reynoso, Juan P.; Arreguín-Sánchez, Francisco; Godínez, Víctor M. (Frontiers in Conservation Science, 2024)
The vaquita (Phocoena sinus) is an endemic species of the Upper Gulf of California (UGC), which is in a critical state of extinction. Bycatch has been considered the main factor leading to its potential extinction; however, the impact of the damming of the Colorado River on the species’ ecology has not been studied. Stable isotopes of carbon (δ13C) and oxygen (δ18O) from vaquita bones were analyzed as indicators of the carbon source of primary producers and habitat use in the UGC from 1982 to 1993. Based on the Colorado River’s flow into the UGC, two periods were markedly different: from 1982 to 1988, when freshwater arrived, and from 1989 to 1993, when the flow was null. Sea surface salinity (SSS) data showed the inverse of the river’s flow pattern, being significantly lower at the end of the 1980s than at the beginning of the 1990s. In agreement with the above, sea surface temperature (SST)/SSS diagrams showed the presence of two water masses inside a gradient from 33.8 to 35.2 psu. The δ13C was significantly different between both periods, with a mean value of -9.1‰ at the end of the 1980s and a mean value of -10.8‰ at the beginning of the 1990s. This means that, when the river flow was dammed, the carbon source of primary producers changed significantly in the UGC. However, the δ18O was not significantly different between both periods, with values of 30.4‰ and 30.5‰, respectively. Comparing the vaquita’s average values of δ18O from this study with those of other marine mammals obtained from previous studies revealed that the vaquita is the most enriched marine mammal species, which could be the result of the high evaporation and salinity that currently occur in the UGC, the vaquita’s habitat. A longer temporal series might show changes in δ18O, which have been detected in other species living in the UGC. From a conservation point of view, the results showed that the impact of environmental variability on the trophic ecology of the vaquita has potential effects on the species’ health.